Whitecoat Adherence in Patients With Primary Open-Angle Glaucoma - Poleon, Shervonne; Sabbagh, Nouran; Racette, Lyne (Frontiers in Medicine, 2022)
Purpose Whitecoat adherence refers to improved medication adherence in the days surrounding clinic visits. This may lead to clinical measures that are not representative of those outside of clinical encounters. In glaucoma, whitecoat adherence to prescribed hypotensive therapy may lead to intraocular pressure readings within the target range, which may impact clinical decision-making. We aimed to quantify and identify factors associated with whitecoat adherence. Methods In this cohort study, patients with primary open-angle glaucoma were selected from an ongoing longitudinal NIH-funded study if they used hypotensive eyedrops, had a clinic visit during the parent study, and had adherence data during the 28 days evenly bracketing the clinic visit. Adherence within the implementation phase was measured using Medication Event Monitoring System (MEMS) caps. Wilcoxon tests were used to compare mean adherence between the following periods: Pre14−4 (days 14 to 4 preceding the clinic visit) and Pre3−1 (days 3 to 1 preceding the visit); Post1−3 (days 1 to 3 following the clinic visit) and Post4−14 (days 4 to 14 following the visit). Analyses were performed in the full sample and in patients with optimal (≥80%, n = 49) and suboptimal adherence (<80%, n = 17). Results Sixty-six patients were included, of which 51.5% were female. Mean age was 70.8 ± 8.1 years. In the 6 months evenly bracketing the clinic visit, mean and median adherence were 86.3% (standard deviation = 17.7) and 95.6% (interquartile range = 21.2), respectively. Overall, mean adherence increased from Pre14−4 to Pre3−1 (85.5% ± 21.2 to 88.5% ± 23.2, p = 0.01) and decreased from Post1−3 to Post4−14 (87.0 ± 23.9 to 84.9 ± 23.3, p = 0.02). In patients with optimal adherence, adherence increased from Pre14−4 to Pre3−1 (94.0 ± 11.7 to 97.7 ± 7.4, p = 0.001) and from Post1−3 to Post4−14 (95.2 ± 12.0 to 95.4 ± 5.7, p = 0.007). Whitecoat adherence was not observed in patients with suboptimal adherence. Conclusion We documented the presence of whitecoat adherence in this cohort. Due to its potential impact on clinical outcomes and decisions, providers should remain vigilant for this phenomenon and prioritize it during patient-provider discussions.